Assistance in Understanding of Financial Literation for Hongkong Immigrant Workers PT. Amal Ichwan Arindo - Ratnawati; Ayu Agustya Ningsih; Yayuk Ngesti Rahayu; M. Taufiq Noor Rokhman; Imam Ropii; Sulis Rahayu (PT FORMOSA CENDEKIA GLOBAL, 2023)
The problem that is often faced by immigrant workers is good financial management when they work abroad. Good financial management is needed when they work with the financial literacy they have with basic knowledge, savings and credit, investment. Wisnuwardhana Malang University provides assistance, providing material on financial literacy in collaboration with PT. Amal Ichwan Arindo which oversees Hong Kong Indonesian Migrant Workers (PMI). Community Service activities are carried out by providing materials and assistance to Indonesian Migrant Workers (PMI) if needed. The method of providing material and assistance is carried out by means of Zoom and providing material directly at the PT. Amal Ichwan Arindo.